Determination of palladium in soil samples by slotted quartz tube-flame atomic absorption spectrophotometry after vortex-assisted ligandless preconcentration with magnetic nanoparticle-based dispersive solid-phase microextraction - Kasa, Nursu Aylin; Sel, Sabriye; Ozkan, Betul Cicek; Bakirdere, Sezgin (SPRINGER, 2019)
In this study, a rapid and effective dispersive solid-phase microextraction (d-SPME) method was developed to preconcentrate Pd from aqueous extract of soil samples by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS). The unique properties of magnetic nanoparticles (MNPs) were used to directly isolate Pd from the sample solutions without the need for complexation. Significant parameters of the extraction method such as magnetic nanoparticle type and amount, pH and amount of buffer solution, amount of eluent, and mixing type and period were optimized together with other instrumental parameters to boost the absorbance signal of Pd. An SQT was fitted onto the burner head to boost the interaction between Pd atoms and hollow cathode lamp radiation to enhance absorbance signals. The limit of detection (LOD) and limit of quantification (LOQ) values for Pd determined (d-SPME-MNP-SQT-FAAS) were 6.4 and 21.4 ng/mL, respectively. The percentage relative standard deviation of the developed method was calculated as 6.6%. The method was applied to soil samples taken from the campus area and spiked recovery experiments were performed to evaluate the method's accuracy/applicability. Satisfactory percent recovery results (90-101%) were obtained for different spiked concentrations and this proved the accuracy/applicability of the method.
Keywords: Palladium; Magnetic nanoparticles; Slotted quartz tube; Flame atomic absorption spectrometry; LIQUID-LIQUID MICROEXTRACTION; WATER; EXTRACTION; SPECTROMETRY; PLATINUM; SOLVENT; DUST; GOLD; Environmental Sciences & Ecology